Kitchen electrical appliances design: Does it influence to the consumer lifestyle? / Mohd Hamidi Adha Mohd Amin and Mohamad Hariri Abdullah - Mohd Amin, Mohd Hamidi Adha; Abdullah, Mohamad Hariri (Universiti Teknologi MARA, Kedah, 2011)
This paper discusses about the influences of kitchen electrical appliance design toward consumer lifestyle. Kitchen electrical appliances are becoming more important towards our daily activity at home. Moreover, it’s become a symbol of quality of life in consumer lifestyle whereby the increasing of technology, function, and design appearance makes it more and not just as for their functions. It has also played an important role as a part of home interior decorations. This paper looks into on how consumers make a decision in selecting kitchen electrical appliances. The selection they made may reflect their lifestyle and their status in the community through design appearance, variation of functions, choices of brands, and ranges of price. Further to that, these appliances can improve their quality of life in term of assisting them in the kitchen. The issue raised is that, there were many previous researches on household electrical appliances regarding the context of consumer decision making, but the studies regarding kitchen electrical appliances design toward consumer lifestyle need to be further elaborated. Therefore, the aim of this paper is to investigate the consumer decision making toward the kitchen electrical appliance, on how they interpret the appearance of kitchen electrical appliance. In order to investigates, this paper uses mixed methods which include quantitative for percentage and qualitative for in-depth information. As a result, it can be concluded that, there are strong bonding and influence factors between kitchen electrical appliances design, consumer lifestyle and their finances. The fact that, the design was created not only to impress the consumer in term of aesthetic alone but also to become their representation in the community.